'Taking the Bank to the Youth': Impacts on Savings from the Ghana YouthSave Experiment. (23rd August 2017) - Lee, Yung Soo; Johnson, Lissa; Ansong, David; Osei‐Akoto, Isaac; Masa, Rainier; Chowa, Gina; Sherraden, Michael
Abstract: This paper explores experimental impacts of in‐school banking and marketing outreach on the savings performance of youth in Ghana. Findings suggest that youth in treatment schools performed better than those in control schools in terms of account opening, depositing and savings. Between the two treatment conditions, in‐school banking was more effective than marketing outreach in promoting savings. These findings demonstrate that a meaningful proportion of low‐income youth, in a resource‐limited country, can be connected to formal financial services and save if access and opportunities are available. The results support the offering of financial services at schools as a strategy to expand youth financial inclusion. Copyright © 2017 John Wiley & Sons, Ltd.